Morozov the story of a family and a lost collection - Semenova, Natalʹja Jurʹevna 1951- (Yale University Press, 2020)
The first English-language account of Ivan Morozov and his ambition to build one of the world's greatest collections of modern art. A wealthy Moscow textile merchant, Morozov started buying art in a modest way in 1900 until, on a trip to Paris, he developed a taste for the avant-garde. Meticulous and highly discerning, he acquired works by the likes of Monet, Pissarro, and Cezanne. Unlike his friendly rival Sergei Shchukin, he collected Russian as well as European art. Altogether he spent 1.5 million francs on 486 paintings and 30 sculptures-more than any other collector of the age. Natalya Semenova traces Morozov's life, family, and achievements, and sheds light on the interconnected worlds of European and Russian art at the turn of the century. Morozov always intended to leave his art to the state-but with the Revolution in 1917 he found himself appointed "assistant curator" to his own collection. He fled Russia and his collection was later divided between Moscow and St. Petersburg, only to languish in storage for decades. Morozov: The Story of a Family and a Lost Collection is being published to coincide with "The Morozov Collection" exhibition at the Fondation Louis Vuitton, Paris, in October 2020
Keywords: Morozov, Ivan A. -- 1871-1921; Sammlung; Kunst; Morozov, Ivan Abramovich; Morozov, Ivan Abramovich / Art collections; Morozov, Ivan Abramovich / Family; Art / Private collections / Russia; Art, European / 20th century; Art, Russian / 20th century; Art, European; Art / Private collections; Art, Russian; Families; Russia; 1900-1999; Biografie